A Subordinated Stochastic Process Model with Finite Variance for Speculative Prices - Clark, Peter K. (Econometrica, 1973)
Thanks are due to Hendrik Houthakker and Christopher Sims, for both encouragement and advice in developing this paper. As usual, all remaining errors are my own. This research was supported by a Harvard Dissertation Fellowship, NSF grant 33-708, and the